Cage-wrapped ball ZnO / ZnFe2O4 superstructure composite material as well as preparation method and application thereof

By using cage-covered ball ZnO/ZnFe2O4 superstructure composite as gas-sensitive material, it regulates its micro-nano structure, and solves the problem of insufficient detection sensitivity for reducing gases such as volatile organic compounds in the prior art, and achieves high sensitivity detection of hydrogen sulfide gas.

CN119750634APending Publication Date: 2025-04-04TONGLING UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411893015.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing metal oxide semiconductor gas sensors have insufficient sensitivity and selectivity to reducing gases such as volatile organic compounds, making it difficult to effectively detect trace amounts of harmful gases.

Method used

The cage-covered ball ZnO/ZnFe2O4 superstructure composite is used as the gas-sensitive material. By regulating the micro-nano structure of the composite material, its detection sensitivity to hydrogen sulfide gas is improved. This material is prepared by reaction of zinc-iron Prussian blue nanocube precursor and metal sulfide to form a cage-covered ball structure with a large specific surface area.

Benefits of technology

It significantly improves the detection sensitivity and selectivity of hydrogen sulfide gas, has stable performance, simple production process, low equipment requirements, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750634A_ABST
    Figure CN119750634A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps that zinc salt is dissolved in diluted hydrochloric acid, a potassium ferricyanide aqueous solution is added into the diluted hydrochloric acid, stirring is conducted till the solution becomes yellow turbid liquid, standing and aging are conducted for 2-36 h at the temperature of 10-95 DEG C, filtering, washing and drying are conducted, and the cage-coated spherical ZnO / ZnFe2O4 superstructure composite material is obtained. The zinc-iron Prussian blue nano cube precursor material is obtained; the preparation method comprises the following steps: dispersing a zinc-iron Prussian blue nano cube precursor material in deionized water, adding a metal sulfide, carrying out a stirring reaction at 5-50 DEG C for 5-30 min, carrying out filtering, washing and drying, and then carrying out annealing at 300-550 DEG C for 1-5 h so as to obtain the cage-coated ball ZnO / ZnFe2O4 superstructure composite material. By regulating and controlling the micro-nano structure of the composite material, the composite material with the cage-wrapped ball structure is obtained, and the structure can improve the detection sensitivity of the composite material as a gas sensitive material to hydrogen sulfide gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to a caged ball ZnO / ZnFe 2 O 4 Superstructure composite material and preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of society, unprecedented economic growth has been promoted. We enjoy all kinds of conveniences in modern metropolises, but we are also facing some negative effects brought by convenient life. Frequent human activities bring various toxic, harmful, flammable and explosive gases, such as volatile organic compounds (VOCs), nitrogen oxides (NO x ), sulfur oxides (SO x ), hydrogen sulfide (H 2 S), etc., pose a continuous threat to environmental safety and human health. Accurate detection of trace harmful gases is crucial to human health and industrial safety. Therefore, the development of highly sensitive and selective gas sensors is of great significance.

[0003] A gas sensor (i.e., a gas sensitive element) is an information device or component that can sense the gas and its concentration in the environment and convert it into an electrical signal, thereby realizing the monitoring, early warning, analysis, and detection of the gas. Among them, the metal oxide semiconductor (MOS) gas sensor has many advantages such as high sensitivity, fast response speed, easy preparation, wide application range, and long service life, and is considered to be an effective solution for the detection of toxic and harmful gases.

[0004] MOS materials are the core of gas sensors. Sensitive materials can be divided into two categories according to whether they involve one or more metal oxides: single metal oxides and composite metal oxides. Single metal oxides have been widely studied as gas sensitive materials, including zinc oxide (ZnO), tungsten trioxide (WO 3 ), ferric oxide (Fe 2 O 3 ), tin dioxide (SnO 2 ), titanium dioxide (TiO 2 ) and other single metal oxides, which are easy to synthesize and have good repeatability, and can efficiently detect a variety of harmful gases. However, the sensitivity and selectivity of single metal oxide semiconductor materials to reducing gases such as volatile organic compounds still need to be improved. Therefore, people try to improve the gas sensing performance by changing the morphology of single metal oxides, metal doping, noble metal modification, and forming heterojunctions with other materials.

[0005] Composite metal oxides are more sensitive to certain gases than single metal oxides. For example, the gas sensing performance of binary metal spinel semiconductor oxides can be improved by changing their microstructure and composition. The general structure of spinel is AB 2 O 4 , where the A position is usually a divalent metal ion and the B position is usually a trivalent metal ion, such as ferrite (AFe 2 O 4 ), chromate (ACrO 4 ) etc. Among them, spinel ferrite (AFe 2 O 4 ) is a sensitive material with excellent chemical and physical stability. Its performance mainly depends on the type, position, and quantity of metal ions in the structure, as well as the material microstructure and specific surface area. Most spinel ferrites exhibit semiconductor properties and have a narrow band gap (~2.0eV). Therefore, designing and synthesizing spinel ferrites with unique structures for the surface catalytic oxidation process of gas sensitive response may significantly improve the gas sensing performance of sensitive materials. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a caged ball ZnO / ZnFe 2 O 4 A superstructure composite material and its preparation method and application; by regulating the micro-nano structure of the composite material, a cage-enclosed ball structure composite material is obtained, and the structure can improve its detection sensitivity to hydrogen sulfide gas as a gas-sensitive material.

[0007] A caged ball ZnO / ZnFe 2 O 4 A method for preparing a superstructure composite material, the method comprising the following steps:

[0008] (1) dissolving a zinc salt in dilute hydrochloric acid, adding an aqueous solution of potassium ferrocyanide thereto, stirring until the solution becomes a yellow suspension, standing and aging at 10 to 95° C. for 2 to 36 hours, filtering, washing, and drying to obtain a zinc-iron Prussian blue nanocube precursor material;

[0009] (2) The zinc iron Prussian blue nanocubic block precursor material is dispersed in deionized water, and metal sulfide is added, and the mixture is stirred at 5-50°C for 5-30 minutes, filtered, washed, and dried, and then annealed at 300-550°C for 1-5 hours to obtain the caged ZnO / ZnFe 2 O 4 Superstructural composites.

[0010] In step (1), the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate.

[0011] In step (1), the molar ratio of potassium ferrocyanide to zinc salt is 1:1.

[0012] In step (1), the concentration of the potassium ferrocyanide aqueous solution is 0.1-2.0 mol / L; the concentration of the zinc salt in dilute hydrochloric acid is 0.1-2.0 mol / L; and the concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.

[0013] In step (1), the static aging condition is preferably 60-80° C. for 12-24 hours.

[0014] In step (2), the metal sulfide is one of sodium sulfide and potassium sulfide.

[0015] In step (2), the mass ratio of the zinc-iron Prussian blue nanocubic block precursor material to the metal sulfide is 1:0.75-2.5.

[0016] In step (2), the concentration of the zinc iron Prussian blue nanocubic block precursor material in deionized water is 0.0015-0.02 g / mL.

[0017] In step (2), the stirring reaction condition is preferably at 20 to 30° C. for 10 to 20 minutes.

[0018] In step (2), the annealing condition is preferably 350-400° C. annealing for 2-3 hours.

[0019] In step (2), the heating rate to the specified annealing temperature is 1 to 6°C / min, preferably 2 to 3°C / min.

[0020] The washing comprises washing the precipitate with deionized water and ethanol at least three times respectively; the drying comprises drying in an oven at 50 to 100° C. for 6 to 24 hours, preferably drying in an oven at 70 to 90° C. for 8 to 15 hours.

[0021] The present invention also provides a caged ball ZnO / ZnFe prepared by the preparation method. 2 O 4 A superstructure composite material, in which nanocages encapsulate nanospheres, has a large specific surface area, and has a stable structure and performance in the air.

[0022] The present invention also provides the caged ball ZnO / ZnFe 2 O 4 Application of superstructure composite materials in gas sensors. The caged sphere ZnO / ZnFe 2 O 4 The superstructure composite material has a very sensitive sensing response to hydrogen sulfide gas.

[0023] The invention provides a caged ball ZnO / ZnFe 2 O 4 In the preparation method of the superstructure composite material, firstly, the prepared orthorhombic system high crystallinity zinc iron Prussian blue nanocubes are used as precursors; then, ion exchange and aging are performed to obtain blue powder zinc sulfide / Prussian blue / zinc iron Prussian blue analogs; finally, heat treatment and oxidation decomposition are performed to obtain caged spheres ZnO / ZnFe 2 O 4 Superstructural composites.

[0024] The chemical reaction formula involved in the reaction process is shown as follows:

[0025] 3Zn 2+ +2Fe(CN) 6 3- →Zn 3 [Fe(CN) 6 ] 2 (1)

[0026] 7Z 3 [Fe(CN) 6 ] 2 + 24S 2- → 21ZnS + 3S + 2Fe 4 [Fe(CN) 6 ] 3 + 48(CN) - (2)

[0027] 2ZnS+2Zn 3 [Fe(CN) 6 ] 2 +57O 2 →6ZnO+2ZnFe 2 O 4 +2SO 2 +24CO 2 +24NO 2 (3)

[0028] The invention obtains zinc iron Prussian blue nano cubic powder by controlling the reaction temperature and the amount of raw materials, which belongs to the orthorhombic system, has high crystallinity and good product quality; and then obtains blue powder zinc sulfide / Prussian blue / zinc iron Prussian blue analogue by ion exchange, and controls the roasting temperature in air to obtain caged ball ZnO / ZnFe 2 O 4 Superstructure composite material; it has large specific surface area, high purity, good product quality, and is highly sensitive to hydrogen sulfide gas in the air.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. Cage ball ZnO / ZnFe 2 O 4 The superstructure composite material is of high purity and does not contain other morphologies;

[0031] 2. Cage ball ZnO / ZnFe 2 O 4 Superstructure composite materials have large specific surface area;

[0032] 3. Cage ball ZnO / ZnFe 2 O 4 The superstructure composite material has stable performance, stable structure and stable performance in the air;

[0033] 4. The production process is simple, with low requirements on equipment, no need for microwaves and surfactants, etc. The raw materials are easily available, the cost is low, and mass production can be carried out. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The caged ball ZnO / ZnFe prepared in Example 1 2 O 4 SEM images of superstructure composite materials;

[0035] Figure 2 The caged ball ZnO / ZnFe prepared in Example 2 2 O 4 SEM images of superstructure composite materials;

[0036] Figure 3 This is a SEM image of the zinc iron Prussian blue nanocube precursor prepared in Example 3;

[0037] Figure 4 This is the XRD pattern of the zinc iron Prussian blue nanocube precursor prepared in Example 3;

[0038] Figure 5 This is a SEM image of the zinc sulfide / Prussian blue / zinc iron Prussian blue analogue prepared in Example 3;

[0039] Figure 6 The XRD pattern of the zinc sulfide / Prussian blue / zinc iron Prussian blue analogue prepared in Example 3;

[0040] Figure 7 The caged ball ZnO / ZnFe prepared in Example 3 2 O 4 SEM images of superstructure composite materials;

[0041] Figure 8 The caged ball ZnO / ZnFe prepared in Example 32 O 4 XRD patterns of superstructure composites;

[0042] Fig. 9 The caged ball ZnO / ZnFe prepared in Example 3 2 O 4 EDS images of superstructure composite materials;

[0043] Fig.10 Example 3: Cage ball ZnO / ZnFe prepared 2 O 4 BET plots of superstructure composites;

[0044] Fig.11 The caged ball ZnO / ZnFe prepared in Example 4 2 O 4 SEM images of superstructure composite materials;

[0045] Fig.12 The caged ball ZnO / ZnFe prepared in Example 5 2 O 4 SEM images of superstructure composite materials;

[0046] Fig.13 ZnO / ZnFe prepared in Comparative Example 1 2 O 4 XRD patterns of heterostructure composites;

[0047] Fig.14 ZnO / ZnFe prepared in Comparative Example 1 2 O 4 SEM images of heterogeneous structure composite materials;

[0048] Fig.15 The caged ball ZnO / ZnFe prepared in Example 3 2 O 4 The superstructure composite material has a high resistance to 10ppm H at an operating temperature of 120℃. 2 The response sensitivity of S and 100ppm different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.);

[0049] Fig.16 ZnO / ZnFe prepared in Comparative Example 1 2 O 4 The heterogeneous structure composite material is resistant to 10ppm H at an operating temperature of 120℃. 2 The response sensitivity of S and 100ppm to different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.). DETAILED DESCRIPTION

[0050] The present invention is described in detail below with reference to the embodiments.

[0051] Example 1

[0052] A caged ball ZnO / ZnFe 2 O 4 The method for preparing a superstructure composite material comprises the following steps:

[0053] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 0.1 M potassium ferrocyanide solution; zinc chloride is dissolved in 0.1 M dilute hydrochloric acid to prepare 1000 mL of a 0.1 M zinc chloride-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc chloride-hydrochloric acid solution under magnetic stirring at a speed of 150 rpm, and then the stirring is continued at room temperature for 5 min to obtain a mixed suspension, which is allowed to stand for aging at 10° C. for 36 h to obtain a yellow precipitate, and the yellow precipitate is filtered, washed, and dried at 50° C. for 24 h to obtain a zinc-iron Prussian blue nanocube precursor;

[0054] (2) 0.2 g of zinc iron Prussian blue nanocube precursor was dispersed in 10 mL of deionized water, 0.15 g of sodium sulfide was added, and the mixture was stirred at 5° C. for 30 min to obtain a blue suspension, which was then dried at 50° C. for 24 h to obtain a blue zinc sulfide / Prussian blue / zinc iron Prussian blue analog;

[0055] (3) The zinc sulfide / Prussian blue / zinc iron Prussian blue analog sample was transferred to a muffle furnace, heated to 300°C at a heating rate of 6°C / min and annealed for 5 h to obtain a khaki-colored ZnO / ZnFe 2 O 4 Superstructure composite material. Its SEM image is as follows Figure 1 As shown, the product morphology is a cage-enclosed ball structure.

[0056] Example 2

[0057] A caged ball ZnO / ZnFe 2 O 4 The method for preparing a superstructure composite material comprises the following steps:

[0058] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 0.5 M potassium ferrocyanide solution; zinc sulfate is dissolved in 0.4 M dilute hydrochloric acid to prepare 1000 mL of a 0.5 M zinc sulfate-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc sulfate-hydrochloric acid solution under magnetic stirring at a speed of 160 rpm, and then the stirring is continued at room temperature for 5 min to obtain a mixed suspension, which is allowed to stand for aging at 30° C. for 30 h to obtain a yellow precipitate, and the yellow precipitate is filtered, washed, and dried at 70° C. for 20 h to obtain a zinc-iron Prussian blue nanocube precursor;

[0059] (2) 0.2 g of zinc iron Prussian blue nanocube precursor was dispersed in 50 mL of deionized water, 0.42 g of potassium sulfide was added, and the mixture was stirred at 15° C. for 20 min to obtain a blue suspension, which was then dried at 60° C. for 20 h to obtain a blue zinc sulfide / Prussian blue / zinc iron Prussian blue analog;

[0060] (3) The zinc sulfide / Prussian blue / zinc iron Prussian blue analog sample was transferred to a muffle furnace, heated to 330°C at a heating rate of 4°C / min and annealed for 4 h to obtain a khaki-colored cage-encapsulated ZnO / ZnFe 2 O 4 Superstructure composite material. Its SEM image is as follows Figure 2 As shown, the product morphology is a cage-enclosed ball structure.

[0061] Example 3

[0062] A caged ball ZnO / ZnFe 2 O 4 The method for preparing a superstructure composite material comprises the following steps:

[0063] (1) Potassium ferrocyanide was dissolved in deionized water to prepare 1000 mL of a 1.0 M potassium ferrocyanide solution; zinc acetate was dissolved in 0.8 M dilute hydrochloric acid to prepare 1000 mL of a 1.0 M zinc acetate-hydrochloric acid solution; the potassium ferrocyanide solution was added to the zinc acetate-hydrochloric acid solution under magnetic stirring at a speed of 160 rpm, and then the stirring was continued at room temperature for 5 min to obtain a mixed suspension, which was allowed to stand for 18 h at 50° C. to obtain a yellow precipitate, which was filtered, washed, and dried at 80° C. for 15 h to obtain a zinc-iron Prussian blue nanocube precursor; its SEM image is shown in FIG. Figure 3 As shown in the figure, it can be seen that it is a uniform cubic block; its XRD pattern is as follows Figure 4 As shown, the diffraction pattern shows that the prepared product is zinc iron Prussian blue (Zn 3 [Fe(CN) 6 ] 2 ·XH 2 O, JCPDS No.38-0687), and has high purity.

[0064] (2) 0.2 g zinc iron Prussian blue nanocube precursor was dispersed in 70 mL deionized water, 0.45 g sodium sulfide was added, and the mixture was stirred at 35° C. for 15 min to obtain a blue suspension, which was then dried at 80° C. for 15 h to obtain a blue zinc sulfide / Prussian blue / zinc iron Prussian blue analogue; its SEM image is shown in FIG. Figure 5 As shown in the figure, it can be seen that it is a cage-enclosed ball structure; its XRD diagram is as follows Figure 6 As shown, all diffraction peaks correspond to the standard cards of zinc sulfide, Prussian blue and zinc iron Prussian blue analogs.

[0065] (3) The obtained zinc sulfide / Prussian blue / zinc iron Prussian blue analog sample was transferred to a muffle furnace, heated to 400°C at a heating rate of 3°C / min and annealed for 3 h to obtain a khaki-colored cage-encapsulated ZnO / ZnFe 2 O 4 Superstructure composite material. Its SEM image is as follows Figure 7 As shown, the product is a cage-enclosed ball structure; its XRD Figure 8 As shown, it can be found that all diffraction peaks are ZnO and ZnFe 2 O 4 The standard card is consistent with that of the product, and there are no other impurity peaks; the EDS diagram of the product is as follows Fig. 9 As shown in the figure, it can be seen that the product contains zinc, iron and oxygen elements, and the silicon element comes from the silicon substrate. Fig.10 As shown, its specific surface area is 44.82m 2 / g, and the average pore size is 3.48nm, indicating that it is a porous material.

[0066] Example 4

[0067] A caged ball ZnO / ZnFe 2 O 4 The method for preparing a superstructure composite material comprises the following steps:

[0068] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 1.5 M potassium ferrocyanide solution; zinc nitrate is dissolved in 1.0 M dilute hydrochloric acid to prepare 1000 mL of a 1.5 M zinc nitrate-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc nitrate-hydrochloric acid solution under magnetic stirring at a speed of 170 rpm, and then the stirring is continued at room temperature for 6 min to obtain a mixed suspension, which is allowed to stand for aging at 75° C. for 8 h to obtain a yellow precipitate, and the yellow precipitate is filtered, washed, and dried at 90° C. for 10 h to obtain a zinc-iron Prussian blue nanocube precursor;

[0069] (2) 0.2 g of zinc iron Prussian blue nanocube precursor was dispersed in 50 mL of deionized water, 0.35 g of sodium sulfide was added, and the mixture was stirred at 40° C. for 10 min to obtain a blue suspension, which was then dried at 80° C. for 12 h to obtain a blue zinc sulfide / Prussian blue / zinc iron Prussian blue analog;

[0070] (3) The zinc sulfide / Prussian blue / zinc iron Prussian blue analog sample was transferred to a muffle furnace, heated to 480°C at a heating rate of 2°C / min and annealed for 2 h to obtain a khaki-colored cage-encapsulated ZnO / ZnFe 2 O 4 Superstructure composite material. Its SEM image is as follows Fig.11 As shown, the product morphology is a cage-enclosed ball structure.

[0071] Example 5

[0072] A caged ball ZnO / ZnFe 2 O 4 The method for preparing a superstructure composite material comprises the following steps:

[0073] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 2.0 M potassium ferrocyanide solution; zinc chloride is dissolved in 1.2 M dilute hydrochloric acid to prepare 1000 mL of a 2.0 M zinc chloride-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc chloride-hydrochloric acid solution under magnetic stirring at a speed of 180 rpm, and then the stirring is continued at room temperature for 10 min to obtain a mixed suspension, which is allowed to stand for aging at 95° C. for 2 h to obtain a yellow precipitate, and the yellow precipitate is filtered, washed, and dried at 100° C. for 6 h to obtain a zinc-iron Prussian blue nanocube precursor;

[0074] (2) 0.2 g of zinc iron Prussian blue nanocube precursor was dispersed in 120 mL of deionized water, 0.5 g of sodium sulfide was added, and the mixture was stirred at 50 ° C for 5 min to obtain a blue suspension, which was then dried at 100 ° C for 6 h to obtain a blue zinc sulfide / Prussian blue / zinc iron Prussian blue analog;

[0075] (3) The zinc sulfide / Prussian blue / zinc iron Prussian blue analog sample was transferred to a muffle furnace, heated to 550°C at a heating rate of 1°C / min and annealed for 1 h to obtain a khaki-colored cage-encapsulated ZnO / ZnFe 2 O 4 Superstructure composite material. Its SEM image is as follows Fig.12 As shown, the product morphology is a cage-enclosed ball structure.

[0076] Comparative Example 1

[0077] According to the method in Example 1 of Chinese Patent CN 104749225 A, ZnO / ZnFe2 O 4 Heterogeneous structure composite material. The XRD pattern of the obtained product is as follows Fig.13 As shown, its SEM image is as follows Fig.14 As shown, the product is a spherical ZnO / ZnFe nanosheet assembly. 2 O 4 Heterostructured composite materials.

[0078] Application Example 1

[0079] Cage Ball ZnO / ZnFe 2 O 4 Application of superstructure composite materials in gas sensors

[0080] The caged ball ZnO / ZnFe prepared in Example 3 2 O 4 Superstructure composite material and ZnO / ZnFe prepared in Comparative Example 1 2 O 4 The composite materials were dispersed in anhydrous ethanol and then evenly coated on a ceramic tube with electrodes to make a gas sensor, which was dried at 50°C for 2 hours and then heat treated at 200°C for 2 hours. Then, a small nickel-chromium alloy coil was placed in the tube as a heater to provide the sensor with an operating temperature. The sensor was aged at 300°C for 48 hours and then tested for different volatile organic gases at the operating temperature. The specific test operation steps are: use a syringe to inject a certain amount of organic vapor into the sensor test box, wait for about 2 minutes, and then introduce dry air into the test box after the sensor output response value stabilizes. The sensor output response gradually recovers, and the output response value of the sensor in dry air and with the target gas is tested and recorded using an electrochemical workstation and a computer. The sensor's sensitivity to gas response is defined as S=R a / R g (reducing gas), R a is the resistance of the sensor in dry air, R g is the resistance of the sensor in the test gas.

[0081] Performance test results show that the prepared caged ball ZnO / ZnFe 2 O 4 Superstructure composite materials have good sensitivity to common toxic and harmful organic gases in the air, such as Fig.15 As shown in the figure, the caged ball ZnO / ZnFe prepared by this method 2 O 4 The superstructure composite material shows good selectivity for hydrogen sulfide compared with different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.), so ZnO / ZnFe 2O 4 As H 2 The sensitive material of S gas is suitable. 2 O 4 Comply with material sensitivity such as Fig.16 By comparison, it is found that the caged ball ZnO / ZnFe 2 O 4 The sensitivity of the superstructure composite material is significantly better than that of the previously reported ZnO / ZnFe 2 O 4 Heterostructured composite materials.

[0082] The above reference embodiment is a cage ball ZnO / ZnFe 2 O 4 The detailed description of the superstructure composite material and its preparation method and application is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the invention should fall within the scope of protection of the invention.

Claims

1. A method for preparing a caged ball ZnO / ZnFe2O4 superstructure composite material, characterized in that: The preparation method comprises the following steps: (1) dissolving a zinc salt in dilute hydrochloric acid, adding an aqueous solution of potassium ferrocyanide thereto, stirring until the solution becomes a yellow suspension, standing and aging at 10 to 95° C. for 2 to 36 hours, filtering, washing, and drying to obtain a zinc-iron Prussian blue nanocube precursor material; (2) The zinc iron Prussian blue nanocubic block precursor material is dispersed in deionized water, and metal sulfide is added. The mixture is stirred at 5-50°C for 5-30 min, filtered, washed, and dried, and then annealed at 300-550°C for 1-5 h to obtain a caged spherical ZnO / ZnFe2O4 superstructure composite material.

2. The preparation method according to claim 1, characterized in that: In step (1), the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate.

3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of potassium ferrocyanide to zinc salt is 1:

1.

4. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the potassium ferrocyanide aqueous solution is 0.1 to 2.0 mol / L; the concentration of the zinc salt in dilute hydrochloric acid is 0.1 to 2.0 mol / L; The concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.

5. The preparation method according to claim 1, characterized in that: In step (2), the metal sulfide is one of sodium sulfide and potassium sulfide.

6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the zinc-iron Prussian blue nanocubic block precursor material to the metal sulfide is 1:0.75-2.

5.

7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the zinc iron Prussian blue nanocubic block precursor material in deionized water is 0.0015-0.02 g / mL.

8. The preparation method according to claim 1, characterized in that: The washing comprises washing the precipitate with deionized water and ethanol at least three times respectively; and the drying comprises drying in an oven at 50 to 100° C. for 6 to 24 hours.

9. The caged ball ZnO / ZnFe2O4 superstructure composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the caged ball ZnO / ZnFe2O4 superstructure composite material as claimed in claim 9 in a gas sensor.

Citation Information

Patent Citations

  • ZnO / ZnFe2O4 composite sensitive material, preparation method thereof and application of ZnO / ZnFe2O4 composite sensitive material in acetone gas sensor

    CN104749225A